Computational Screening of Single Atoms Anchored on Defective Mo2CO2 MXene Nanosheet as Efficient Electrocatalysts for the Synthesis of Ammonia. Issue 10 (22nd July 2021) - Wang, Shuo; Li, Lei; San Hui, Kwan; Bin, Feng; Zhou, Wei; Fan, Xi; Zalnezhad, E.; Li, Jing; Hui, Kwun Nam
Abstract : The electrochemical nitrogen reduction reaction (NRR) over single‐atom catalysts (SACs) anchored on Mo vacancies of Mo2 CO2 MXene nanosheets under ambient conditions suffers from poor selectivity, low yield, and low Faradaic efficiency because of their sluggish kinetics and the competing hydrogen evolution reaction. Herein, density functional theory calculations are performed to improve the understanding of the selectivity and yielding of ammonia through NRR over various isolated SACs, that is, from Sc to Au, anchored on the Mo vacancy of the Mo2 CO2 MXene nanosheet (denoted as MO2 CO2 ‐MSA ). The potential‐determining step of the NRR shows that eight candidates (i.e., Y, Zr, Nb, Hf, Ta, W, Re, and Os) confined on the defective Mo2 CO2 layer could promote the electroreduction from N2 to NH3 . Among these, Mo2 CO2 ‐YSA presented the lowest reported reaction Presents the lowest reported reaction energy barrier (0.08 eV) through the distal pathway and high selectivity to NRR compared with the previously synthesized Mo2 CO2 ‐RuSA with a relatively high energy barrier (0.65 eV) and poor selectivity. In addition, the formation energy of Mo2 CO2 ‐YSA is more negative than that of the Mo2 CO2 ‐RuSA catalyst, suggesting that the experimental preparation of the Mo2 CO2 ‐YSA catalyst is highly feasible. This work lays a solid foundation for improving the rational design of MXene‐based systems as efficient electrocatalysts for the synthesis of ammonia. Abstract : The single‐atom Y anchored on defective Mo2 CO2 shows the lowest reported reaction energy barrier (0.08 eV) through the distal pathway and high selectivity to the nitrogen reduction reaction. Electronic combinations of filled and empty d orbitals of the transition metals promote the activation of N2 .